2017
DOI: 10.1080/23262133.2017.1302216
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of the study of nerve dependent regeneration

Abstract: Nerve dependence is a phenomenon observed across a stunning array of species and tissues. From zebrafish to fetal mice to humans, research across various animal models has shown that nerves are critical for the support of tissue repair and regeneration. Although the study of this phenomenon has persisted for centuries, largely through research conducted in salamanders, the cellular and molecular mechanisms of nerve dependence remain poorly-understood. Here we highlight the near-ubiquity and clinical relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 90 publications
(90 reference statements)
0
52
0
Order By: Relevance
“…In 1956, Holtzer conducted an extensive histological study of tail regeneration with and without the spinal cord (Holtzer, ). The study found that similar to limb regeneration (for review see Farkas and Monaghan, ), tail regeneration cannot proceed without nerves and spinal ganglia alone cannot promote outgrowth, outlining the requirement for the spinal cord. Holtzer then rotated the spinal cord before tail amputation and found that the surrounding cartilaginous rod differentiated on the dorsal side of the spinal cord rather than the usual ventral side (Holtzer, ).…”
Section: Similarity Between Tail and Limb Regenerationmentioning
confidence: 84%
“…In 1956, Holtzer conducted an extensive histological study of tail regeneration with and without the spinal cord (Holtzer, ). The study found that similar to limb regeneration (for review see Farkas and Monaghan, ), tail regeneration cannot proceed without nerves and spinal ganglia alone cannot promote outgrowth, outlining the requirement for the spinal cord. Holtzer then rotated the spinal cord before tail amputation and found that the surrounding cartilaginous rod differentiated on the dorsal side of the spinal cord rather than the usual ventral side (Holtzer, ).…”
Section: Similarity Between Tail and Limb Regenerationmentioning
confidence: 84%
“…neuregulin) and vascular (e.g. VEGF) regeneration (Yu et al, 2014;Farkas et al, 2016;Farkas and Monaghan, 2017;Ritenour and Dickie, 2017) were active in the wound epidermis, yet suppressed in regenerating stump tissues, signifying that early neurovascular regeneration is coordinated by the wound epidermis and that repression of these pathways within regenerating stump tissues may be important. A potential explanation for this apparent dichotomy lies in the timing of activation.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the salamander body can compute the severity of trauma and distinguish between a minor injury and amputation. Additionally, severed nerves at the site of amputation are necessary for blastema cell proliferation, as denervation prevents blastema growth and consequently limb regeneration (Farkas and Monaghan, 2017). In the event of an amputation, only the missing part of the limb will regrow, which is the region distal to the wound site (Stocum, 2017).…”
Section: Insights From Studying Regeneration In Salamanders Mechanismmentioning
confidence: 99%